Influence of principals’ role, teachers’ ICT skills, and infrastructure management on quality of education - Dian Novika Dewi; Ngasbun Egar; Rosalina Br. Ginting (Curricula: Journal of Curriculum Development, 2025)
This study was motivated by the fact that the quality of education in public vocational high schools (SMK) in Blora Regency remains suboptimal. Several factors influence the quality of education, including the role of school principals, teachers’ information and communication technology (ICT) competence, and the management of facilities and infrastructure. The objective of this research was to analyze the influence of these three variables, both individually and in combination, on the quality of education. A quantitative ex post facto design was employed. The population consisted of 383 teachers from public vocational schools in Blora, with 196 teachers selected using a proportional random sampling method. Data were collected through a Likert-scale questionnaire and analyzed using simple and multiple linear regression with SPSS 29. The findings revealed that school leadership, teachers’ ICT competence, and facilities management have a positive and significant effect on education quality, both individually and collectively. These results indicate that while the three variables are important, education quality is also shaped by other external factors. In conclusion, improving the quality of education in Blora’s vocational schools requires strengthening school leadership, enhancing teachers’ digital literacy, optimizing facilities management, and fostering broader collaboration with stakeholders.   Abstrak Penelitian ini dilatarbelakangi oleh mutu pendidikan SMK Negeri di Kabupaten Blora yang masih belum optimal. Faktor yang memengaruhi mutu pendidikan antara lain peran kepala sekolah, kemampuan teknologi informasi dan komunikasi (TIK) guru, serta manajemen sarana prasarana. Tujuan penelitian ini adalah menganalisis pengaruh ketiga variabel tersebut baik secara parsial maupun simultan terhadap mutu pendidikan. Penelitian menggunakan pendekatan kuantitatif jenis ex post facto. Populasi penelitian adalah seluruh guru SMK Negeri di Kabupaten Blora sebanyak 383 orang, dengan sampel 196 guru dipilih secara proportional random sampling. Data dikumpulkan menggunakan angket skala Likert, kemudian dianalisis dengan regresi linier sederhana dan berganda menggunakan SPSS 29. Hasil penelitian menunjukkan bahwa kepemimpinan kepala sekolah, kompetensi TIK guru, serta manajemen sarana prasarana berpengaruh positif dan signifikan terhadap mutu pendidikan, baik secara parsial maupun simultan. Temuan ini mengindikasikan bahwa meskipun peran ketiga variabel penting, mutu pendidikan juga dipengaruhi faktor lain di luar model penelitian. Kesimpulannya, peningkatan mutu pendidikan SMK Negeri di Kabupaten Blora dapat dilakukan melalui penguatan kepemimpinan kepala sekolah, peningkatan literasi digital guru, pengelolaan sarana prasarana yang lebih optimal, serta dukungan dari berbagai pemangku kepentingan. Kata Kunci: kemampuan tik guru; kepala sekolah; mutu pendidikan; sarana prasarana